Bridging the Gap: Enhancing Science Learning for Social Science Students - de Deus, João Mariano Helder (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
Many social science students at the Instituto Católico para a Formação de Professores (ICFP) Baucau, Timor-Leste, face difficulties when studying natural science in their second year because of their different academic backgrounds. This study aims to explore strategies that make natural science learning more accessible and engaging for these students. Using a literature review of recent research, the paper examines teaching methods that enhance motivation and understanding. Key approaches include hands-on experiments, clear explanations, interactive activities, and the use of real-life examples connected to students’ social and cultural contexts. The findings show that when science lessons are simplified, contextualized, and linked to practical experiences, students become more motivated and confident in their learning. These strategies not only improve comprehension but also make science more meaningful for learners from non-science backgrounds. The study provides recommendations for teachers at ICFP Baucau to design inclusive and engaging lessons that support social science students in successfully learning natural science